An approach on the role of government in the context of an Islamic state: religion and politics - Kayadibi, Saim (Global Academic Excellence, 2018)
A system that is not formed by specific values, such as justice, trust, accountability and so forth, cannot sustain its existence. History provides both secular and revelation-based government systems, the latter of which is often found within the Islamic world in the past. Islam’s governing system is not limited to specific forms and policies in order to rely upon specific principles. The style of governance may turn out to be good or bad, effective or ineffective, depending upon whether the religion’s values or the ruler’s self-desires are implemented. Due to the political instability in Islamic countries, it creates confusion in the administration and the role of government. The objective of this paper is to highlight the significant role of the government and the governance through the concept of state in Islamic law by analysing the concept of the sharī‘ah-oriented public policy (siyāsah sharī‘ah). Content analysis research method is used in this conceptual paper by collecting data from library and secondary resources. This paper, therefore, intended to contribute to the academic research related to the government and the concept of state of siyāsah sharī‘ah by identifying the appointment and qualities of officials, leadership, and the organs of the state, such as the consultation body (shūrā), public orders (ḥisbah), and undetermined punishment (ta‘zīr) by developing the concept of state as the seventh value of the maqāṣid al-sharī‘ah in order to achieve a successful government system.